EAD415 : Visualization techniques / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This course require analytical and conceptual visualization skills in order to transform abstract thought efficiently into graphic, tangible forms and to manage the topic complexity and the problems addressed in each class. The key for visualization techniques and methods are to provide visualization principles and exercises for students’ experiences.